Coastal floods in the Mediterranean. Trasformation strategies for resilient cities - Carmela Mariano; Marsia Marino (Agathón)
The IPCC 2018 report represents the current state of knowledge on climate change and its potential environmental and socio-economic impacts. One of the most direct consequences of these changes is represented by the raising of the sea-level, the topic on which the contribution lingers, highlighting how, to date, there is no declination, at the local planning level, of the content addresses in the sectoral tools responsible for managing the phenomenon. The contribution, starting from the results of a recent ENEA research, explores the territorial context of the Mediterranean, specifically the Italian area, to bring out some methodological and operational suggestions for the elaboration of some possible strategies for transforming urban contexts affected by flooding.